Income Tax Fundamentals 2020, 38th Edition - Gerald E. Whittenburg; Martha Altus-Buller; Steven Gill (Cengage Learning, 2019)
Learn the complexities of the U.S. income tax code and master the most important areas of tax law with Whittenburg/Altus-Buller/Gill's market-leading INCOME TAX FUNDAMENTALS 2020. This concise, practical introduction to today's tax preparation uses a unique, step-by-step workbook format that integrates actual tax forms. A clear presentation presents the most up-to-date tax changes and developments as you walk through real examples using current, authentic tax forms. A variety of end-of-chapter problems offer hands-on practice, including tax return problems that use source documents identical to those of real clients. Turn to INCOME TAX FUNDAMENTALS 2020 to refine the timely knowledge and practical skills you need to become a successful tax preparer. Important Notice: Media content referenced within the product description or the product text may not be available in the ebook version.